Moving the Spotlight from Plagiarism to Academic Integrity in Paraphrasing Instruction - Rossi, Silvia Luisa (Canadian Perspectives on Academic Integrity, 2021)
For higher education students completing research-based assignments, paraphrasing is an essential skill. While instructors often expect students to be reasonably proficient in paraphrasing by the time they finish high school, the reality is that many students arrive at college or university never having experienced explicit instruction in paraphrasing. They have certainly used paraphrasing in their previous academic work, but their understanding of this critical skill rarely goes beyond the basic notion that paraphrasing means “saying it in your own words,” and many believe that synonym substitution is paraphrasing. Once students embark on their post-secondary journey, paraphrasing instruction is still rare, but the stakes are immediately higher. Through dire warnings on course outlines and in assignment instructions, students quickly learn to associate paraphrasing with plagiarism, and the resulting fear can prevent them from becoming excited about joining the academic conversation. In the paraphrasing workshops offered by university and college writing centres, practice opportunities may be limited to short, decontextualized transformation activities, which can inadvertently reinforce the common but misguided belief among students that effective source integration is a matter of skimming the first few pages of a source for a useful target sentence to slot into a pre-existing argument. This session will describe how writing specialists at one undergraduate university are shifting their approach to paraphrasing instruction. Practice activities that prioritize contextualization and writer agency are helping students discover the power of paraphrasing. By de-emphasizing plagiarism and instead focusing on the values of academic integrity, this new approach aims to help students view themselves as members of discourse communities - members who have a responsibility to deeply engage with and fairly represent one another’s work.